PDR for herbal medicines. - Thomson Healthcare (Firm) (Montvale, NJ : Thomson, 2007)
Provides information on scientific and common names, characteristics, active compounds, clinical effects, indications, usage, clinical research, precautions, interactions, and dosage for over seven hundred herbs.
Alphabetical index -- Therapeutic category index -- Indications index -- Homeopathic indications index -- Asian indications index -- Side effects index -- Drug/herb interactions guide -- Safety guide -- Common herbal terminology -- Herb identification guide -- Herbal monographs -- Nutritional supplement monographs.
Includes bibliographical references and indexes.
Keywords: Materia medica, Vegetable -- Handbooks, manuals, etc; Herbs -- Therapeutic use -- Handbooks, manuals, etc; Medicinal plants; Phytotherapy